2016
DOI: 10.1038/srep21416
|View full text |Cite
|
Sign up to set email alerts
|

LPS/TLR4-mediated stromal cells acquire an invasive phenotype and are implicated in the pathogenesis of adenomyosis

Abstract: The present study tested whether the LPS/TLR4 signal pathway in endometrial stromal cells is essential for the pathogenesis of adenomyosis. We tested the expression of TLR4, MD2 in the endometrium without adenomyosis (CE), the eutopic endometrium with adenomyosis (EuE) and the ectopic endometrium with adenomyosis (EE). We isolated the stromal cells from CE, EuE and EE (CESC, EuESC, EESC), treated with lipopolysaccharide (LPS) and TLR4 antagonist and detected the cell viability. And we also measured the key pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 56 publications
(59 reference statements)
0
38
0
Order By: Relevance
“…Emerging evidence suggested that this disease may be linked to the expression of inflammatory mediators and the induction of an immune response (4)(5)(6). A previous study by our group has confirmed that lipopolysaccharide (LPS) stimulates inflammatory cell proliferation and invasive growth of stromal cells in adenomyosis by activation of the Toll-like receptor (TLR4)/myeloid differentiation primary response gene 88/nuclear factor (NF)-κB signaling pathway, indicating that LPS/TLR4 signaling is implicated in the pathogenesis of adenomyosis (7). This provided a novel therapeutic strategy for adenomyosis via targeting TLR4 signaling.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…Emerging evidence suggested that this disease may be linked to the expression of inflammatory mediators and the induction of an immune response (4)(5)(6). A previous study by our group has confirmed that lipopolysaccharide (LPS) stimulates inflammatory cell proliferation and invasive growth of stromal cells in adenomyosis by activation of the Toll-like receptor (TLR4)/myeloid differentiation primary response gene 88/nuclear factor (NF)-κB signaling pathway, indicating that LPS/TLR4 signaling is implicated in the pathogenesis of adenomyosis (7). This provided a novel therapeutic strategy for adenomyosis via targeting TLR4 signaling.…”
Section: Introductionmentioning
confidence: 87%
“…The improper inflammatory response induced by LPS/TLR4 signaling has the potential to cause inflammatory disorders (24,25). Various studies have indicated that local and chronic inflammatory reactions in the uterus and peritoneal environment are likely to be associated with the pathogenesis of endometriosis/adenomyosis (7,26,27). Azuma et al (26) reported that LPS promoted the development of endometriosis through the NF-κB pathway in a murine model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stimulation by lipopolysaccharide (LPS), a major component of the outer membrane of Gram-negative bacteria, can lead to local infections or inflammatory processes through the Toll-like receptor 4 (TLR4)-mediated signalling pathway89. TLR4, a receptor for LPS, is one of the strongest inducers of inflammation10.…”
mentioning
confidence: 99%